Peningkatan Taraf Hidup Kaum Dhuafa melalui Program Pesantren Dhuafa Baznas Kota Yogyakarta di Kelurahan Muja Muju, Umbulharjo, Kota Yogyakarta - Abdullah bin Edi; Ahmad Baily (Da'wa Faculty IAIN Purwokerto, 2021)
This study discusses the Dhuafa Islamic Boarding School Program organized by BAZNAS Yogyakarta City. The Dhuafa Islamic Boarding School program is held in the month of Ramadan. The purpose of this research is first to find out the program of activities aimed at the poor. Second, to find out the results of the program of activities on the quality of life of the poor who become santri in the poor Pesantren. This research uses a qualitative descriptive research type. The subjects in this study were the poor who became students at the orphanage boarding school. The data collection method used in this research is the method of interview, observation, and documentation. The type of observation in this study uses an involved type of observation. Meanwhile, in analyzing this research, the writer uses the ideas put forward by Pijono and Pranarka regarding the concept of empowerment. The results of this study show that the form of improving the living standards of the poor through the Pesantren program for the poor organized by BAZNAS Yogyakarta is in the form of students getting motivation, self-awareness to improve their work ethic and quality of life. These poor people also gain knowledge about religion and have the ability to read the Qur’an